The Joan Miró Foundation and its collections. - Malet, Rosa Maria; Fundacio Joan Miro, Barcelona (Barcelona : Fundació Joan Miró, 1990)
The Joan Miró Foundation and its collections ; Origins and aims ; The buiding ; The collections ; Activities
boek
Keywords: Miro, Joan